Excavations by Gogar Church, Nether Gogar, Edinburgh (Scottish Historical and Archaeological Internet Reports, 2018)
This report records the results of an excavation of a medieval settlement next to Gogar Church (NGR: NT 16827 72540) that was discovered within the construction corridor of the Edinburgh Tram line. The remains relate to the medieval village of Nether Gogar and date from the 11th to the 15th century, although later material was also recovered. The results of this work complement previous work on the site of Nether Gogar (Morrison et al 2009) and add to the growing evidence of medieval rural settlement in the Edinburgh area.